Evaluation of KRASG12C inhibitor responses in novel murine KRASG12C lung cancer cell line models - Sisler, Daniel J.; Hinz, Trista K.; Le, Anh T.; Kleczko, Emily K.; Nemenoff, Raphael A.; Heasley, Lynn E. (Frontiers in Oncology, 2023)
The KRAS(G12C) mutation is the most common genetic mutation in North American lung adenocarcinoma patients. Recently, direct inhibitors of the KRASG12C protein have been developed and demonstrate clinical response rates of 37-43%. Importantly, these agents fail to generate durable therapeutic responses with median progression-free survival of ~6.5 months. To provide models for further preclinical improvement of these inhibitors, we generated three novel murine KRASG12C-driven lung cancer cell lines. The NRASQ61L gene in KRASG12C-positive LLC cells was deleted and the KRASG12V allele in CMT167 cells was edited to KRASG12C with CRISPR/Cas9 methods. Also, a novel murine KRASG12C line, mKRC.1, was established from a tumor generated in a genetically-engineered mouse model. The three lines exhibit similar in vitro sensitivities to KRASG12C inhibitors (MRTX-1257, MRTX-849, AMG-510), but distinct in vivo responses to MRTX-849 ranging from progressive growth with orthotopic LLC-NRAS KO tumors to modest shrinkage with mKRC.1 tumors. All three cell lines exhibited synergistic in vitro growth inhibition with combinations of MRTX-1257 and the SHP2 inhibitor, RMC-4550. Moreover, treatment with a MRTX-849/RMC-4550 combination yielded transient tumor shrinkage in orthotopic LLC-NRAS KO tumors propagated in syngeneic mice and durable shrinkage of mKRC.1 tumors. Notably, single-agent MRTX-849 activity in mKRC.1 tumors and the combination response in LLC-NRAS KO tumors were lost when the experiments were performed in athymic nu/nu mice, supporting a growing literature showing a role for adaptive immunity in the response to this class of drugs. These new models of murine KRASG12C mutant lung cancer should prove valuable for identifying improved therapeutic combination strategies with KRASG12C inhibitors.